How Temporary Book Tax Differences Influence Earning Quality? An Integrated Analysis with Investment Opportunity Set and Human Capital - Jacobus Widiatmoko; Maria Goreti Kentris Indarti; Luluk Muhimatul Ifada (Universitas Pendidikan Ganesha, 2023)
We examined three variables, including the differences of temporary book tax, investment opportunity sets, and human capital to recognize if any of these variables have different impact on earnings quality. The population use of this research is manufacturing companies listed on the Indonesia Stock Exchange in 2017-2021. Based on the purposive sampling technique, a total of 338 data were obtained. By using ordinary least square technique of analysis, the test results reveal that the differences of temporary book tax have a negative impact on quality of earnings and the investment opportunity set has a positive impact on quality of earnings. Meanwhile, human capital has no impact on quality of earnings. Our study provides insight that the differences of temporary book tax and investment opportunity sets are important information that must be considered by investors in analyzing the quality of company earnings, so that investment provides optimal returns.